BACE1 Activity Is Modulated by Cell-Associated Sphingosine-1-Phosphate - Takasugi, Nobumasa (J Neurosci, 2011)
Sphingosine kinase (SphK) 1 and 2 phosphorylate sphingosine to generate sphingosine-1-phosphate (S1P), a pluripotent lipophilic mediator implicated in a variety of cellular events. Here we show that the activity of β-site APP cleaving enzyme-1 (BACE1), the rate-limiting enzyme for amyloid-β peptide (Aβ) production, is modulated by S1P in mouse neurons. Treatment by SphK inhibitor, RNA interference knockdown of SphK, or overexpression of S1P degrading enzymes decreased BACE1 activity, which reduced Aβ production. S1P specifically bound to full-length BACE1 and increased its proteolytic activity, suggesting that cellular S1P directly modulates BACE1 activity. Notably, the relative activity of SphK2 was upregulated in the brains of patients with Alzheimer's disease. The unique modulatory effect of cellular S1P on BACE1 activity is a novel potential therapeutic target for Alzheimer's disease.